The role of Zakat as an Islamic social finance towards achieving sustainable development goals: a case study of Northern Nigeria - Ibrahim Atah, Ummi; Mohammad Ali Nasr, Wafa; Mohammed, Mustafa Omar (1st Global Conference on Islamic Economics and Finance 2018 (GCIEF 2018), 2018)
Purpose: This study aims to explore the role of Zakat in addressing development challenges facing Nigeria and its potentiality in achieving sustainable development goals in Nigeria. Design/methodology/approach: The study adopts qualitative method by conducting library research and critically reviewing the literature. Findings: This study finds that Zakat as an Islamic social finance for ensuring socioeconomic and distributive justice through preserving and circulating wealth, has the potentialities of achieving most sustainable development goals. This includes reduction of poverty, hunger and inequality. In addition, zakat can promote sustainable agriculture, peaceful and inclusive societies, quality education, good health and well-being. Therefore, the study concludes that, to ensure effective utilisation of zakat fund by the recipient and wider coverage of Zakat to a number of poor people in the region, utilisation of modern communication in form of e-community-based platform for enlightment towards investment of zakat fund in the form of Mudaraba is mandatory. This approach is also found to be useful in enhancing financial inclusion of poor people and diversification of sources of zakat collection. Originality/value: The novelty of this study lies in the incorporation of E-community based platform structure for collection, distribution and investment of certain percentage of recipient fund in the form of Mudaraba. Limitation: The research is limited to library research and covers the whole Northern Nigeria without specific reference. More so the perception of the stakeholders is not taken into cognisance. Further Research: Further research should carry out a field survey to gauge the perception of the stakeholders with regard to the proposed e-community-based platform by making reference to a particular state. Practical implications – Study findings can be useful to policymakers in diversifying sources of Zakat collection and effective disbursing of Zakat to reduce poverty, inequality and hunger. Social implications – The target zakat beneficiary are generally poor, the study outcome may improve their total welfare and quality of life.